2021
DOI: 10.3390/su132413669
|View full text |Cite
|
Sign up to set email alerts
|

Artificial Intelligence-Driven Digital Technologies to the Implementation of the Sustainable Development Goals: A Perspective from Brazil and Portugal

Abstract: Innovativeness is a characteristic of digital technologies (DT), and they have been assuming an important role in economic, social, and environmental dimensions. Therefore, DT are relevant contributors for sustainable development goal (SDG) achievements. This study aims to compare the preference for artificial intelligence-driven digital technologies (AI-Driven DT) to achieve SDGs in Brazil and Portugal. An independent sample t-test analysis and Levene test are performed to identify potential artificial intell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 87 publications
0
11
0
1
Order By: Relevance
“…In study (Pigola, 2021), confirmed that digital technologies (DT) are characterized by innovation, and that they have played a key role in economic, social, and environmental dimensions. As a result, DT are important contributors to the achievement of the Sustainable Development Goals (SDGs).…”
Section: -Literature Reviewmentioning
confidence: 67%
“…In study (Pigola, 2021), confirmed that digital technologies (DT) are characterized by innovation, and that they have played a key role in economic, social, and environmental dimensions. As a result, DT are important contributors to the achievement of the Sustainable Development Goals (SDGs).…”
Section: -Literature Reviewmentioning
confidence: 67%
“…After the data collection phase, the next stage involved the evaluation of the economic and environmental results of the implementation of CP, to address the proposed research questions. The instruments used to evaluate the economic and environmental results, as recommended by [34,[54][55][56][57][58][59] followed the methodology for the environmental evaluation of the implementation of Eco efficiency tools in industrial operations. A first step involved the collection of data to identify the reduction in waste and emissions, by means of a mass balance method, offering detail about the materials and the components and calculation of the Total Saved Materials (MTE).…”
Section: Methodsmentioning
confidence: 99%
“…AI brings huge potential to accelerate the green energy transition [154][155][156], but its current application is limited to pilots, with barriers to scaling up. AI applications for energy cover consist of high-fidelity models for predicting renewable generation and demand, grid and systems optimization, operation and maintenance, demand management and innovation [157][158][159]. Virtual Power Plants can boost distributed energy and automation of small, distributed devices such as electric vehicles [153,160].…”
Section: Group 3: Ai As a DImentioning
confidence: 99%
“…In addition, a relevant limitation of this analysis relies on the potential bias induced when selecting datasets [159], applying black-box algorithms and when evaluating interactions and impacts based on expert opinions and pilots whose results are difficult to extrapolate and could lead to spurious conclusions [52]. In conclusion, there exists a burgeoning research landscape and huge opportunities but also several caveats, data and reporting gaps, lack of accountability, and limited literature on the contribution of AI to most SDG metrics that merit further research.…”
Section: Group 3: Ai As a DImentioning
confidence: 99%
See 1 more Smart Citation